Agribusiness Development of Flavor Rice “Mandoti” in Enrekang Districts - Omar Khayam Khayam; Dr.Irmayani Irmayani; Amaluddin Amaluddin (Sangia Publishing, 2020)
Enrekang Regency is one of the areas in South Sulawesi with a topography of producing vegetable commodities, but apart from that this area also produces superior commodities that are only produced in Salukanan Village, Baraka District, namely local rice flavored rice known as